The impact of transport and foreign direct investment on energy consumption: recent evidence from high, middle and low income countries. (2017) - Saidi, Samir; Badri, Rabaa; Hammami, Sami
This paper investigates the impact of various macroeconomic variables on energy use. Among these variables, we are interested in the specific impacts of transport and foreign direct investment in 68 countries over the period 2000-2014. In order to make the panel data analysis more homogeneous, we also investigate the interrelationships for a number of sub-panels which are constructed based on the income level of countries. In this way, we end up with three income panels; namely, high-income, middle-income and low-income panel. By applying the Generalised Method of Moments (GMM) on a dynamic panel data model, the results indicate that the energy consumption is affected positively and significantly by the freight transport in all panels. However, the impact of foreign direct investment is positive and significant for the high-income and middle-income panels. For the low-income panel, the impact is positive and insignificant. Finally, the energy use is positively correlated with economic growth, population and capital stock with different levels of significance.